1997
DOI: 10.20955/wp.1997.003
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence on Returns to Scale and Product Mix Among U.S. Commercial Banks

Abstract: Numerous studies have found that banks exhaust scale economies at low levels ofoutput, but most are based on the estimation of parametric cost thnctions which misrepresent bank cost. Here we avoid specification error by using nonparametric kernel regression techniques. We modify measures of scale and product mix economies introduced by Berger et al. (1987) to accommodate the nonparametric estimation approach, and estimate robust confidence intervals to assess the statistical significance of returns to scale. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 0 publications
4
78
4
Order By: Relevance
“…Through Table 6, we also found that the characteristics variable LTA has no significant correlation with BHCs' profitability and risk, and this has been proved by some empirical studies which have shown that there is not necessarily economies of scale among commercial banks, such as Wheelock andWilson (1997), McNulty (2000). LCAR has significantly positive correlation with BHCs' profitability and risk, NCO can notably affect banks' performance in a negative way and influence banks' risk positively.…”
Section: Full Sample Data Empirical Studiesmentioning
confidence: 71%
“…Through Table 6, we also found that the characteristics variable LTA has no significant correlation with BHCs' profitability and risk, and this has been proved by some empirical studies which have shown that there is not necessarily economies of scale among commercial banks, such as Wheelock andWilson (1997), McNulty (2000). LCAR has significantly positive correlation with BHCs' profitability and risk, NCO can notably affect banks' performance in a negative way and influence banks' risk positively.…”
Section: Full Sample Data Empirical Studiesmentioning
confidence: 71%
“…In addition, several studies (e.g. McAllister and McManus, 1993;Wheelock and Wilson, 2001) show that the Translog does not fit well when banks are of widely varying sizes. 11 Observations of doubtful reliability, and banks that did not report information for some of the variables necessary for estimating the indicators of competition were eliminated from the sample.…”
Section: Sample and Variablesmentioning
confidence: 99%
“…We do not test to see the importance of bank size on cost as many studies have shown that larger banks in Europe and elsewhere generally have lower unit costs than smaller institutions due to realized scale economies (c.f., Altunbas et al, 2001;Schure et al, 2004;Wheelock and Wilson, 2001). Instead, using recent data covering a set of large banks across 10 countries in Europe over 1996-2002, we seek to determine the relative importance that business environmental influences and variations in internal productivity may have in explaining cross-country differences in bank efficiency.…”
Section: Introductionmentioning
confidence: 99%